2000
DOI: 10.14411/eje.2000.071
|View full text |Cite
|
Sign up to set email alerts
|

Unconditioned and conditioned responses to colour in the predatory coccinellid, Harmonia axyridis (Coleoptera: Coccinellidae)

Abstract: Abstract. We determined if mature ladybirds use colour to initially find suitable host plants. We also determined whether ladybird beetles are capable of associating characteristics such as colour with the presence of prey. Here, we show that the multicoloured Asian ladybird beetle, Harmonia axyridis, has a differential response to yellow compared to green colours. Naive ladybirds, of both sexes, make significantly more visits and spend more time on yellow vs. green coloured pillars. After pairing yellow and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 21 publications
(22 reference statements)
2
28
0
Order By: Relevance
“…The presence of this species might have resulted in hoverfl ies being equally distributed across the different treatments. Moreover, ladybeetles and hoverfl ies are sensitive to colour, especially yellow (Sutherland et al, 1999;Mondor et al, 2000). Hoverfl ies are also sensitive to fl owers with a contrasting UV-pattern (Koski & Ashman, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this species might have resulted in hoverfl ies being equally distributed across the different treatments. Moreover, ladybeetles and hoverfl ies are sensitive to colour, especially yellow (Sutherland et al, 1999;Mondor et al, 2000). Hoverfl ies are also sensitive to fl owers with a contrasting UV-pattern (Koski & Ashman, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When traits are considered in the environment in which a plant grows, they may affect ecological processes, and are qualifi ed as functional (Dıáz & Cabido, 2001). Several studies have explored the effect of fl ower traits on the behaviour of natural enemies using laboratory experiments, monospecifi c plots in fi elds or plants in pots (Mondor & Warren, 2000;Schaller & Nentwig, 2000;Fiedler & Landis, 2007b;Miller et al, 2013;Van Rijn & Wäckers, 2016). The shape of the corolla is another fl ower trait, which determines how insects access the food provided by fl owers.…”
Section: Methodsmentioning
confidence: 99%
“…Although visual cues are likely to be involved (Lambin et al, 1996), olfactory cues are considered more important for prey location by H. axyridis (Obata, 1986;Mondor and Warren, 2000;Sloggett et al, 2011). When seeking prey, ladybeetles increase their walking speed and reduce their turning frequency.…”
Section: Prey Locationmentioning
confidence: 99%
“…Larvae and adults showed long and short distance visual perception (Lambin et al 1996), with adults exhibiting better visual perception than larvae. Mondor and Warren (2000) showed that adults were attracted to the color yellow more than to the color green. However, if they were conditioned to receiving food with one of the colors, then females tended to spend more time on the color associated with food.…”
Section: Prey Searching and Predationmentioning
confidence: 99%